Família, pobreza e renda no Paraná - Ramos, Sonia Aparecida Gomes de (2022)
The aim of the study was to identify and analyze the impacts of recent changes observed in the structure of families and their relationship with poverty. The object of study is the state of Paraná, with geographic coverage of the Immediate Geographical Regions (RGI), comparing rural and urban areas. The used methodology was the estimation of a Family Multidimensional Poverty Index (IPMF), using data from IPARDES, with an excerpt between 2006 and 2016. The survey results indicate that the state showed an increase in the number of families from 2006/2010 of 1% and 8% between 2010/2016. From the 29 RGIs, 17 of these were considered urban areas with a share of the agricultural GDP between 5% and 20%, while there are 12 rural areas with a share of the GDP between 21% and 37%. Regarding the classification of the sex of individuals, predominance of adult females. In children and teenagers, the percentage was higher in males, an average of 4%. The rural regions had an average per capita GDP between R$ 17,000.00 and R$ 32,000.00 and the urban ones between R$ 22,000.00 and R$ 48,000.00. Regarding the IPMF, the results indicate that poverty has been decreasing over the period, although with oscillations showing a reduction in the indexes and a subsequent increase. In the infant mortality dimension, a decrease of -0.52% in urban RGIs and -0.3% in rural ones. In the illiteracy dimension, urban areas have 22.16%, more illiterates than in rural regions, however there was a reduction of -1.74% from 2006 to 2016 in urban areas and -1.49% in rural areas. In the income dimension between 2006 and 2016, urban areas present a reduction of - 0.43%, and in rural areas it was - 3.89%. In the undernutrition dimension, both regionalizations had a considerable decrease until 2015, and 3% average increase for 2016. The proportion of poor people (H) in urban regions was higher than in rural regions, except for the year 2016, which presented a proportion of poverty lower than that of rural regions by 0.66%. The intensity of poverty in 2006 was 1.08% in rural regions and 0.99% in urban areas. Deprivation in rural regions between 2006 and 2016 increased by 0.45%. In urban regions, multidimensional family poverty in 2006 was 33.95%; 2010 of 33.91% and 2016 of 33.99%. In rural areas 2006 of 34.03%; 2011 of 34.08% and in 2016 of 33.92%. The analysis allows us to conclude that the dimensions and indicators have higher percentages, in most of the determinant variables in urban regions, than in rural regions. The conclusion is that there have been changes in family demography and the presence of poverty in Paraná.